THE CONVERSATIONAL IMPLICATURE OF PODCAST ENTITLED “THE TRUTH ABOUT MONEY AND HAPPINESS” WITH DR SANA SAJAN - Ira Febriyanti Simanjuntak; Charles David Marudut Silalahi; Shancelldeep Kaur (Jurnal Cakrawala Ilmiah, 2025)
This study examines the conversational implicature in the podcast episode "The Truth About Money and Happiness," featuring Dr. Sana Sajan. Utilizing a qualitative descriptive approach and content analysis, the research applies Grice (1975) theory of implicature to explore how implicit meanings and linguistic nuances in Dr. Sajan's discourse link abstract concepts—such as emotional fulfillment and financial stability—with tangible life experiences. Particular emphasis is placed on the role of Grice's conversational maxims—quality, quantity, relation, and manner—in enhancing listener comprehension and fostering engagement. This investigation seeks to illuminate how these pragmatic devices contribute to the delivery of complex ideas in accessible ways for the audience.